REGIONAL DIALECTOLOGY (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article extensively discusses the theoretical and practical foundations of regional dialectology. In particular, it analyzes the phonetic, lexical, and grammatical features of dialects formed in different regions. The historical development of dialectology, scientific schools, and modern research methods are described. The study explores regional dialects of the Uzbek language, their differences, and their influence on the standard language. The relevance of the topic is also highlighted in terms of language preservation, the study of cultural heritage, and language policy.